Simple Strategy for Scalable Preparation Carbon Dots: RTP, Time‐Dependent Fluorescence, and NIR Behaviors. Issue 5 (28th December 2021) - Bai, Jianliang; Yuan, Guojun; Chen, Xu; Zhang, Lu; Zhu, Yaqing; Wang, Xinyu; Ren, Lili
Abstract: Transforming carbon dots (CDs) fluorescent materials into smart materials with complex functions is a topic of great interest to nanoscience. However, designing CDs with regulating fluorescence/phosphorescence that can be visually monitored with the environment changes in real‐time remains a challenge. Here, a very simple strategy, one‐step solvent‐free catalytic assistant strategy, which is low cost, facile, environment‐friendly, and high throughput, is put forward. Hydrogen bond is used to manipulate nanostructure of CDs, and the obtained carbon dots (M‐CDs) show a series of attractive properties including matrix‐free room‐temperature phosphorescence, time‐dependent fluorescence, and near‐infrared emissive characteristics. Different from the traditional aggregation caused quenching or aggregation‐induced emission fluorescent materials, M‐CDs exhibit unprecedented and unique dispersion induced redshift fluorescence phenomenon, promoting the studies of fluorescence from static to dynamic. The causes of this phenomenon are further analyzed in detail. As a kind of intelligent fluorescent materials, this new designed CDs greatly enrich the basic recognition of CDs by illustrating the relationship between redshift fluorescence behaviors and the dispersion states, and may provide with an opportunity for solid‐state fluorescent materials, anti‐counterfeiting, cellular imaging, and hopefully many others. Abstract : Illustration of simple solvent‐free catalytic assistant strategy for scalable preparation smart and versatile carbon dots (matrix‐free room‐temperature phosphorescence, time‐dependent fluorescence, and near‐infrared behaviors).